2015
DOI: 10.1177/2374289515614003
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Milestones

Abstract: All Accreditation Council for Graduate Medical Education accredited pathology residency training programs are now required to evaluate residents using the new Pathology Milestones assessment tool. Similar to implementation of the 6 Accreditation Council for Graduate Medical Education competencies a decade ago, there have been challenges in implementation of the new milestones for many residency programs. The pathology department at the University of Iowa has implemented a process that divides the labor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…1 Additionally, milestones were adopted to monitor resident progression throughout their training. 2 , 3 While the ACGME has broadly advocated for these quality control measures, only one published study has reported quality improvement in a surgical pathology resident rotation curriculum by implementing a point system to limit grossing an excess volume of cases. 4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, milestones were adopted to monitor resident progression throughout their training. 2 , 3 While the ACGME has broadly advocated for these quality control measures, only one published study has reported quality improvement in a surgical pathology resident rotation curriculum by implementing a point system to limit grossing an excess volume of cases. 4 …”
Section: Introductionmentioning
confidence: 99%